Totaldigteren Grundtvig En kommenteret forskningshistorisk oversigt som bidrag til bestemmelsen af Grundtvigs egenart som digter - Christensen, Bent (Grundtvig-Studier, 2011)
Totaldigteren Grundtvig: En kommenteret forskningshistorisk oversigt som bidrag til bestemmelsen af Grundtvigs egenart som digter [The Total Poet Grundtvig. A commented survey of the history of literary Grundtvig research as a contribution to the understanding of Grundtvig 's character as a poet] By Bent Christensen In his Omkring Grundtvigs Vidskab (About Grundtvig’s Vidskab: An Inquiry into N. F. S. Grundtvig’s View of the Knowledge Aspect of the Commitment to Life that Is a Necessary Part of Christianity), the author first and foremost sees Grundtvig as a “kirkelig og folkelig totaldigter” (total poet of the church and the people). The term “total poet” is analogous to “total theatre”, in which the spectator is drawn into the drama and the actors mingle with the audience. An extensive examination of the poetic aspect of the said commitment is desirable but outside the scope of this article. This commented survey of the literary Grundtvig research and criticism therefore presents some key points in the understanding of Grundtvig as a “total poet”. First, following an exchange of views with Poul Borum regarding the various attempts to use Grundtvig for certain purposes, there is an analysis of the extended text of Gustav Albeck’s lecture “Har Grundtvig-Selskabet forsømt Digteren Grundtvig?” (Has the Grundtvig Society Neglected the Poet Grundtvig?). Albeck provides an overview of the Grundtvig literary research and criticism from the nineteenth century till Poul Borum’s book Digteren Grundtvig (Grundtvig the Poet), and he shows that the study of Grundtvig’s poetry requires a different approach than that of usual literary criticism and research. Next, Albeck’s own contribution Omkring Grundtvigs Digtsamlinger (About Grundtvig’s Collections of Poems) is dealt with. Albeck especially calls attention to Grundtvig’s half jocular characterisation of himself as a “deponentisk digter” (deponent poet - the term “deponent” from Latin grammar indicating passive form and active meaning in verbs). It is pointed out that the active side of Grundtvig’s efforts eventually developed into an actual historical and political interactive commitment increasingly centring on the idea of “Folkelighed” (meaning both what comes from and what pertains to “the people”). In Grundtvigs Symbolverden (Grundtvig’s Universe of Poetic Symbols), Helge Toldberg focuses on mapping all main symbols which Grundtvig since 1814/15 constantly draws upon in his poetry. From his chosen perspective of theories on symbolism, Toldberg registers a number of connections and associations which are also being considered in Omkring Grundtvigs Vidskab. Already in Fra drøm til program (From Dream to Programme: The Place and Significance of Human Life and Its World in the Theology of N. F. S. Grundtvig), the author agrees with Flemming Lundgreen-Nielsen’s understanding of the year 1819 as the year when Grundtvig places himself totally outside ordinary poetry. And he also agrees with Lundgreen-Nielsen in so far as his concept “selvsymbolik” (self-symbolism) is concerned. But according to the author, the literary scholar Flemming Lundgreen-Nielsen does not go sufficiently deep into the matter when sticking to the question as to whether Grundtvig, despite his unique character, still has a sense of common literary poetic factors. The contrast between “aesthetics” and “poetry” in Grundtvig’s works is not only a contrast between the “total poet Grundtvig” and “aesthetics” but also a contrast between the merely “aesthetic” and the poetical depth dimension as a whole. But Flemming Lundgreen-Nielsen provides an apt expression of Grundtvig’s unique character as a poet when saying in Det handlende ord (The Operative Word: The Poetry, Literary Criticism and Poetics of N. F. S. Grundtvig 1798-1819) (1980) that Grundtvig’s book is composed as a progression from the 15-year-old schoolboy’s exercise books to “Grundtvig understood by himself as a symbolic character in the history of Denmark”. In Digteren Grundtvig (Grundtvig the Poet), Poul Borum looks upon Grundtvig as a “total poet”, stressing above all his qualities as a “poet” and taking a “total poetic” view of him as the prophet bard (“skjalde-profeten”). Finally, Hans Hauge’s reply to Poul Borum called “Alt-i-alt” (All in all) is considered. Hauge’s conception of Borum’s book as belonging to the aesthetic and literary 1980s, placed between the political 1970s and the universalising 1990s, seems particularly interesting. However, it is hard to tell Hauge’s own notion of Grundtvig as a poet. In conclusion, the author suggests that it is specific to Grundtvig that, for one thing, within a peculiar historical vision or construction and in a peculiar, highly unified, symbolic world, he conducts an extensive and continuous interweaving of the nation and his own fate, and that, for another, Christianity is almost always included in his poetry.